2011
DOI: 10.1038/ng.874
|View full text |Cite
|
Sign up to set email alerts
|

A20 (TNFAIP3) deficiency in myeloid cells triggers erosive polyarthritis resembling rheumatoid arthritis

Abstract: A20 (TNFAIP3) is a protein that is involved in the negative feedback regulation of NF-κB signaling in response to specific proinflammatory stimuli in different cell types and has been suggested as a susceptibility gene for rheumatoid arthritis. To define the contribution of A20 to rheumatoid arthritis pathology, we generated myeloid-specific A20-deficient mice and show that specific ablation of Tnfaip3 in myeloid cells results in spontaneous development of a severe destructive polyarthritis with many features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
255
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 262 publications
(286 citation statements)
references
References 30 publications
18
255
2
1
Order By: Relevance
“…The functions of A20 are diverse and cell type-dependent: myeloid cells require A20 to prevent their spontaneous hyperactivation and expansion 9 , while IECs need A20 as a protective factor maintaining barrier stability in inflammatory conditions 8 . Although single IEC or myeloid deletion does not cause spontaneous intestinal defects, double IEC and myeloid A20 deficiency induces spontaneous intestinal pathology due to hyperinflammatory A20-deficient myeloid cells causing epithelial apoptosis and progressive loss of Paneth and goblet cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The functions of A20 are diverse and cell type-dependent: myeloid cells require A20 to prevent their spontaneous hyperactivation and expansion 9 , while IECs need A20 as a protective factor maintaining barrier stability in inflammatory conditions 8 . Although single IEC or myeloid deletion does not cause spontaneous intestinal defects, double IEC and myeloid A20 deficiency induces spontaneous intestinal pathology due to hyperinflammatory A20-deficient myeloid cells causing epithelial apoptosis and progressive loss of Paneth and goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, A20 myel-KO mice develop rheumatoid arthritis-like symptoms, but not colitis, due to hyperactivated myeloid cells producing elevated levels of inflammatory cytokines, including TNF and interleukin-6 (IL-6) (ref. 9). Combined IEC and myeloid A20 deficiency (A20 IEC/myel-KO ) fully recapitulates the inflammatory phenotype of A20 myel-KO mice, showing myeloid cell expansion with lymphadenopathy and splenomegaly, and increased levels of TNF and IL-6 in their serum ( Supplementary Fig.…”
Section: A20 Iec/myel-ko Mice Develop Spontaneous Intestinal Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides a framework for understanding the role of A20 in suppressing B-cell lymphomas, which is suggested by human genetic studies (36,96,161). Other studies have found critical functions for A20 in dendritic cells (83,126), macrophages (167), and intestinal epithelial cells (265).…”
Section: Otu Familymentioning
confidence: 99%